Pengaruh pendapatan asli daerah, dana alokasi umum, kredit konsumsi terhadap pertumbuhan ekonomi: Studi kasus di Provinsi Sumatera Selatan tahun 2006-2015 - Lingga Nopita Sari; Didik Susetyo; M. Syirod Saleh (Jurnal Ekonomi Pembangunan, 2016)
This research was conducted to determine the effect of Regional Original Income (PAD), General Allocation Funds (DAU) and Consumption Credit on Economic Growth Study in Two Districts and Two Cities in South Sumatra Province in 2006-2015. This study aims to empirically examine the Effect of Regional Original Revenue, General Allocation Funds, and Consumer Loans on Economic Growth. The data used in this study are secondary data from 2006-2015 the location of this research was conducted in Lahat District, Musi Banyuasin Regency, Palembang City and Pagar Alam City. This research was carried out by using the Least Square (PLS) Data Regression Panel using Eviews 8.0. The final model selection used in this research was the Fixed Effect Model. The results of this study indicate that Regional Original Revenue, General Allocation Funds, Consumer Loans simultaneously influence Economic Growth. Partially Regional Original Revenue, General Allocation Funds, Consumer Loans have a positive and significant effect on Economic Growth. From the results of the estimation model, it is known that the value of the Determination Coefficient (R2) is 0.999868, this means that independent variables such as Regional Original Income, General Allocation Funds and Consumption Credit have been able to explain what happened to the dependent variable Economic Growth of 99.98% while the other 0.02% is explained by other variables not included in the regression model. The final results of this study, show that Local Revenue, General Allocation Funds, Consumer Credit can explain the changes that occur in the dependent variable of Economic Growth